Development of Discovery-Based Nervourssy Media on the Topics of Nervous System to Improve Digital Literacy and Critical Thinking Skills - Purwanti, Purwanti; Subiantiro, Agung Wijaya (FKIP Universitas Lampung, 2024)
This research aims to determine the characteristics, feasibility and effectiveness of Nervourssy learning media based on discovery learning on the nervous system material to improve students’ digital literacy and critical thinking skills. This research is Research and Development (R&D) research which refers to the ADDIE development model, which consists of 5 stages, namely: analysis, design, development, implementation and evaluation. The limited trial subjects were 22 students and the field test subjects were 65 students from two classes. The field test was carried out using a quasi-experiment with a pretest-posttest control group design. The data collection instruments used were interviews, observations, feasibility assessment sheets, digital literacy ability observation sheets and critical thinking ability test instruments. The results of the research show that: (1) The characteristics of Nervourssy learning media based on discovery learning have interactive content so that it becomes an attraction for students, an emphasis on group discussions, and a complete integration of the discovery learning model so as to encourage students to be actively involved in the learning process by searching, investigating and formulating their own findings; (2) Nervourssy learning media based on discovery learning on nervous system material is feasible and practical to use in the learning process; (3) Nervourssy learning media based on discovery learning on nervous system material is effective in improving digital literacy and critical thinking skills. Based on the paired-sample t-test, digital literacy skills in the control class did not experience a significant increase (P=0.888), while the experimental class experienced a significant increase (P=0.000). Meanwhile, critical thinking abilities in the control (P=0.022) and experimental (P=0.022) classes experienced significant improvement. Independent sample t-test results for digital literacy skills (P=0.001) and critical thinking skills (P=0.000) Keywords: learning media, discovery learning, nervous system material, digital literacy, critical thinking.DOI: http://dx.doi.org/10.23960/jpmipa/v25i2.pp620-636